Effect of hemp content and clay stabilization on hygric and thermal properties of hemp-clay composites. (20th September 2021) - Mazhoud, Brahim; Collet, Florence; Prétot, Sylvie; Lanos, Christophe
Highlights: The density of composites is higher with stabilized clay for the same hemp content. The hemp to binder ratio impacts density, thermal conductivity and sorption curve. Hemp clay composites are excellent hygric regulators and good insulation materials. A correlation between hemp to binder ratio and water content is identified. Innovative analysis of hemp and binder contribution to water sorption is performed. Abstract: The objective of this paper is to investigate the effect of clay stabilization and hemp content on hygric and thermal performances. This experimental study is based on the measurement of sorption isotherm, moisture buffer value and thermal properties. The effect of water content on thermal conductivity is also investigated. The results show that Hemp Clay Composites (HCC) and Hemp Stabilized Clay Composites (HSCC) are hygroscopic and moisture buffering materials. The correlations between hemp content and water content are identified for sorption curves. An innovative analysis of the contribution of hemp and binder to water sorption is performed. The moisture buffer values classify the designed composites as excellent hygric regulators according to the Nordtest classification. The thermal conductivity ranges from 0.089 to 0.120 W/(m.K) at dry state, making them suitable for distributed insulation. The thermal conductivity increases linearly with density, for the two binders investigated in this study. Besides, the thermal conductivity increases linearly with water content too. Finally, this study underlines that the designed composites show high hygrothermal qualities.